2008
DOI: 10.1089/fpd.2008.0106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of AI-2/LuxS–Dependent Transcription inCampylobacter jejuniStrain 81-176

Abstract: Autoinducer-2 (AI-2) is a quorum-sensing signal molecule that controls a variety of cellular activities in response to cell density in both gram-negative and gram-positive bacteria. The production of AI-2 is dependent upon LuxS, the last enzyme in the AI-2 biosynthesis pathway. For this study, we constructed a luxS null mutation (Delta luxS) in Campylobacter jejuni strain 81-176, and showed that it abolished AI-2 production. The Delta luxS mutant had a longer doubling time in Mueller-Hinton (MH) broth and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 51 publications
11
79
3
Order By: Relevance
“…Increased expression of perR, which is known to negatively regulate ahpC, is somewhat paradoxical, and may indicate the existence of alternative regulators of ahpC (van Vliet et al, 1999). Recent microarray data suggest that the luxS gene, putatively encoding an autoinducer-2 biosynthetic enzyme, increases the expression of ahpC and tpx, suggesting that these genes could be under the control of quorum-sensing signals (He et al, 2008). Phenotypic studies of C. jejuni stress responses in different growth phases have, however, proved inconclusive and further work is needed to establish the details of C. jejuni stress responses during stationary phase and their regulation Klanĉnik et al, 2006;Murphy et al, 2003Murphy et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of perR, which is known to negatively regulate ahpC, is somewhat paradoxical, and may indicate the existence of alternative regulators of ahpC (van Vliet et al, 1999). Recent microarray data suggest that the luxS gene, putatively encoding an autoinducer-2 biosynthetic enzyme, increases the expression of ahpC and tpx, suggesting that these genes could be under the control of quorum-sensing signals (He et al, 2008). Phenotypic studies of C. jejuni stress responses in different growth phases have, however, proved inconclusive and further work is needed to establish the details of C. jejuni stress responses during stationary phase and their regulation Klanĉnik et al, 2006;Murphy et al, 2003Murphy et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…sembly/regulation genes including flgD, flgE, fliD, fliS, flgR, flgI, flgK, flaA, flgG2 but not flaB or flhA [14]. In contrast, microarray analysis of a C. jejuni NCTC 11168 luxS mutant grown for 8 h at 42 °C performed by Holmes et al [43] indicated a reduced expression profile of 15 flagellar genes including 12 genes which were shown to be up-regulated in the study by He et al [14].…”
Section: Motility and Chemotaxismentioning
confidence: 90%
“…While C. jejuni luxS mutants showed nearly the same growth rate and motility as wild type strains at 42 °C, a minor reduction of growth rate and decreased motility on soft agar was described at 37 °C [14,32,35,41,42]. It has been shown that flaA but not flaB transcription was reduced in a C. jejuni 81116 luxS mutant, grown for 24 h at 42 °C, although the FlaA and FlaB proteins as well as the total flagellar protein amounts and the flagellar structure seemed to be unaffected [41].…”
Section: Motility and Chemotaxismentioning
confidence: 91%
See 2 more Smart Citations